Vibration response analysis and hoop layout optimization of spatial pipeline under random excitation - Wang, Donghai; Sun, Wei; Gao, Zhihui; Li, Hui (Aircraft engineering, 2022)
Purpose In many cases, the external pipelines of aero-engine are subjected to random excitation. The purpose of this paper is to reduce the vibration response of the pipeline system effectively by adjusting the hoop layout. Design/methodology/approach In this paper, a spatial pipeline supported by multi-hoops is taken as the object, the methods of solution of the vibration response of the pipeline system by using pseudo excitation and hoop layouts optimization with amplitude reduction of vibration response as the goal are presented. First, the finite element model of the spatial pipeline system is presented. Then, an optimization model spatial pipeline is established. Finally, a case study is carried out to prove the rationality of the random vibration response analysis of the pipeline system. Furthermore, the proposed optimization model and genetic algorithm are applied to optimize the hoop layout. Findings The results show that the maximum response variance after optimization is reduced by 32.8%, which proves the rationality of the developed hoop layout optimization method. Originality/value The pseudo excitation method is used to solve the vibration response of aero-engine pipeline system, and the optimization of the hoop layout for aero-engine spatial pipelines under random excitation to reduce random vibration response is studied systematically.